Forum on food systems and obesity in Latin America and the Caribbean (LAC) - Díaz-Bonilla, Eugenio; Rapallo, Ricardo; Intini, Joao; Paz, Florencia; Hernández, Yenory (International Food Policy Research Institute, 2018)
As a start for the joint work program, FAO and IFPRI organized a meeting of experts and stakeholders to discuss the structure and linkages between the current operation of food systems and their impact on overweight and obesity levels in the population of Latin America and the Caribbean. The main objective of the joint work program is to help LAC countries develop and implement efficient and equitable policy options and interventions that can turn around current trends towards increases in obesity and overweight of their population. A particular focus of the program will be to look at the causes that hinder the access to healthy foods of the poorest and most vulnerable sectors of the population, either due to the lack of physical availability of such foods, their high prices, or the inherent cultural or social conditions of the most vulnerable population groups, which make them live in unhealthy food environments or choose unhealthy food patterns. It will also consider the production, employment, income and poverty implications of the potential changes in food systems needed to end hunger and all forms of malnutrition by 2030.